Pengaruh Emotional Value terhadap Customer Satisfaction Studi Kasus pada Pelanggan: Restoran Saoenk Kito Jambi - Yulia Angraini, Tri; Hamdaini Putri, Yulia; Welly Nailis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was conducted with the aim of determining the influence of 4 dimensions of customer value, namely emotional value, social value, performance value and price value on customer satisfaction at the Saoenk Kito Jambi restaurant. This research uses primary data. In this research data collection technique, a survey technique was used using a questionnaire instrument. The population in this research is all customers who have made transactions at the Saoenk Kito restaurant in Jambi with a sample of 100 respondents. In this research, the measurement scale used is the Likert scale. The data analysis techniques used in this research are multiple linear regression analysis and hypothesis testing using SPSS version 2.6 software. The conclusion results of this research show that partially 3 dimensions of customer value, namely emotional value, performance value and price value, have a significant positive effect on customer satisfaction at the Saoenk Kito Jambi restaurant, 1 dimension of customer value, namely social value, partially has no positive effect on customer satisfaction. The variables emotional value, social value, performance value and price value simultaneously have a significant effect on customer satisfaction.